Komputerisasi Sistem Pembayaran Iuran Bulanan Untuk Usaha dan Perusahaan Berbasis Client - Server (Studi Eksperimen pada Kantor Desa Dauh Puri Klod) - IGN Alit Widana Putra; IGN Manik Nugraha (LPPM Universitas Dhyana Pura, 2015)
This research aim to apply the information technology at process of fee collection to entrepreneur and company at office of countryside of dauh puri klod. This research will be executed at Office of Countryside of Dauh Puri Klod. This Research type is quasi eksperiment, with the device of posttest only control group design. Sampel used by entire/all effort and company amounting to 581 object, what [is] gone the round of in 11 Orchard / banjar. Data collecting conducted with the structure observation and not structure. Analysis technique used in this research is analysis varians (anava) one band. Result expected in this research is a application base on the client - server to assist the process of data processing and print the receipt of fee collection to the effort and company at Office of Countryside of Dauh Puri Klod become more effective and efficient.Keywords : application client - server, system of collection of monthly fee to the effort andcompany.